2018
DOI: 10.1590/s0004-2803.201800000-25
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Is Increased in Individuals With Crohn’s Disease: A Comparative Analysis With Healthy Controls

Abstract: -Background -It is known that obesity is associated with a chronic inflammatory state, but few studies have evaluated visceral fat (VF) content and its role in individuals with Crohn's disease (CD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
0
24
0
2
Order By: Relevance
“…More recently, these investigations have utilized improving imaging and body composition measurement technologies to concentrate specifically on the role of lean tissue and adipose tissue, especially visceral fat, in CD. These have included magnetic resonance imaging (MRI) computed tomography (CT) and, as used in our study, bioimpedance 31 or DEXA 32 . As with our results, most studies determine levels of sarcopenia or relatively low lean tissue indices, combined with elevated adiposity in patients with CD, sometimes correlating with low skeletal mass 33 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, these investigations have utilized improving imaging and body composition measurement technologies to concentrate specifically on the role of lean tissue and adipose tissue, especially visceral fat, in CD. These have included magnetic resonance imaging (MRI) computed tomography (CT) and, as used in our study, bioimpedance 31 or DEXA 32 . As with our results, most studies determine levels of sarcopenia or relatively low lean tissue indices, combined with elevated adiposity in patients with CD, sometimes correlating with low skeletal mass 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Independently of the general fat mass accumulation, VAT depot has been highlighted as a major risk factor for developing several metabolic, cardiovascular, autoimmune, neurodegenerative, and oncological diseases, as well as an increased risk for early mortality (Van Gaal et al, 2006 ; Cereda et al, 2007 ; Fontes-Carvalho et al, 2014 ; Yu et al, 2015 ; Brown et al, 2017 , 2018 ; Dan Lantsman et al, 2018 ; Kuritzkes et al, 2018 ; Magro et al, 2018 ). The Authors reported a significant relationship between the identified anthropometric tools assessing total and regional adiposity and several health issues, including glucose dysregulation, insulin resistance, metabolic syndrome, cardiometabolic dysregulation, type 2 diabetes, hypertension, cardiovascular diseases, cancer, as well as a higher risk of early cardiovascular and all-cause mortality (Piqueras et al, 2021 ).…”
Section: Health Issues Associated With Obesity Relationship To the Anthropometric Assessment Toolsmentioning
confidence: 99%
“…Yet, in order to manage a disease, we need first to diagnose it. Obesity diagnosis requires to have available easy to use and accurate tools to measure total and regional body fat storage, in particular visceral adiposity, major risk factor of developing obesity related comorbidities (Nicklas et al, 2006 ; Van Gaal et al, 2006 ; Cereda et al, 2007 ; Anan et al, 2010 ; Fontes-Carvalho et al, 2014 ; Yu et al, 2015 ; Brown et al, 2017 , 2018 ; Han et al, 2017 ; Dan Lantsman et al, 2018 ; Kuritzkes et al, 2018 ; Magro et al, 2018 ; Tian et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other conditions linking obesity and CD include: changes in food-intake behavior, increased consumption of industrialized food and animal fat/protein, decreased dietary fiber intake as well as reduction in physical activity [38]. Treatments used for IBD, in particular corticosteroids and anti-TNF-α therapies, have been implicated in weight-gain [39].…”
Section: And Obesitymentioning
confidence: 99%